Response of Soil Organic Carbon and Its Aggregate Fractions to Long-Term Fertilization in Irrigated Desert Soil of China - Yan-jun CHAI; Xi-bai ZENG; E Sheng-zhe; Tao HUANG; Zong-xian CHE; Shi-ming SU; Ling-yu BAI (Journal of Integrative Agriculture, 2014)
Irrigated desert soil samples in the Hexi Corridor of China were collected over a period of 23 years from a site where different fertilization methods had been used. Changes of soil organic carbon (SOC) and its water stable aggregate (WSA) size fractions were studied. The effects of various fertilization methods on the distribution of added organic carbon (OC) in different WSA size fractions were also analyzed. The results showed that the applied fertilizations for 23 years improved SOC concentrations and OC concentrations in all WSA size fractions compared to the non-fertilized treatment (CK). In addition, fertilization obviously increased the OC stocks of <2 mm WSA size fractions compared to the CK. The average OC stock of <0.053 mm WSA fraction was 1.7, 1.6 and 3.2 times higher than those of >2 mm, 0.25-2 mm and 0.053-0.25 mm WSA fractions, respectively. A significant positive correlation was found between soil C gains and OC inputs (r=0.92, P<0.05), indicating that SOC may have not reached the saturation point yet at the site. The C sequestration rate was estimated by 14.02% at the site. The OC stocks in all of the <2 mm WSA fractions increased with the increase of OC input amounts; and the conversion rate of the input fresh OC to the OC stock of <0.053 mm WSA fraction was 1.2 and 2.6 times higher than those of the 0.25-2 mm and 0.053-0.25 mm WSA fractions, respectively. Therefore, the <0.053 mm WSA fraction was the most important component for soil C sequestration in the irrigated desert soil.